ANALISIS SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN SISTEM PENGKURAN KINERJA PADA PT PLN (PERSERO) UP3 MAKASSAR SELATAN - Endang Sulistiani; Ismail Badollahi; Abd Salam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Endang sulistiani. 105731109821. Title: Analysis of Management Accounting Information Systems and Performance Measurement Systems at PT PLN (Persero) UP3 South Makassar. Thesis, Accounting Department, Faculty of Economics and Business, Muhammadiyah University of Makassar. Supervised by Ismail Badollahi and Abd Salam. This study aims to analyze the implementation of Management Accounting Information System (MAIS) and the effectiveness of performance measurement systems at PT PLN (Persero) UP3 Makassar Selatan. The research is motivated by the importance of integrating accurate and real-time information systems to support managerial decision-making and organizational performance evaluation. This study uses a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation from employees directly involved in the use of MAIS and performance measurement systems. The results show that the implementation of the ERP-SAP-based MAIS at PT PLN (Persero) UP3 Makassar Selatan has successfully supported managerial processes, particularly in terms of reporting efficiency, information accuracy, and cross-functional integration including finance, HR, and asset management. The performance measurement system in place is also considered effective, utilizing MAIS data for work achievement monitoring and evaluation, although some technical challenges remain. This research is expected to provide insights for improving information systems and performance measurement in state-owned enterprises.